Intensification of Land and Building Acquisition Tax (BPHTB) Collection in Semarang City Based on Semarang City Regional Regulation Number 2 of 2011: Intensifikasi Pemungutan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) di Kota Semarang Berdasarkan Perda Kota Semarang Nomor 2 Tahun 2011 - Rina Leidyawaty Silitonga (Universitas Negeri Semarang, 2012)
BPHTB is one kind of Local Taxes to be optimized. Optimization can be done with the intensification BPHTB BPHTB collection. The research aims to find an intensification of collection charges of acquiring land rights and buildings (BPHTB) in the city of Semarang Semarang by regulation No. 2 of 2011. These results indicate that the inventory of relevant regulations in the city of Semarang BPHTB can be classified into two periods, Shape DPKAD intensification conducted by the city of Semarang is to increase the frequency of execution, improve quality, and research tighten Tax Payment Area (SSPD) BPHTB. There are arrears that can not be solved by DPKAD the city, is still a lack of awareness of the WP and the lack of public knowledge about BPHTB. Strategy taken in the collection BPHTB intensification in the city of Semarang is a persuasive approach to the WP; cooperation with the National Land Agency in the city of Semarang, PPAT, and auction officials; attend the exhibition in the knowl-check property’s market value. As a recommendation to the city of Semarang DPKAD to provide a sustainable BPHTB related socialization that people know and understand the provisions of BPHTB in Semarang. Performance and cooperation with relevant parties in the implementation of BPHTB should be improved to optimize BPHTB.